Odpowiedzi

2009-10-17T15:06:29+02:00
2x-⅕ + 3y-2/4=2
{
3x+⅕ - 3y+2/4=0

5x = 2 / :5
x = ⅖

3x+⅕ - 3y+2/4=0
{
x = ⅖

3 * ⅖ + ⅕ - 3y + ½ = 0
{
x = ⅔

3y = 19/10
{
x = ⅔

y = 19/30
{
x = ⅔
2009-10-17T16:00:37+02:00
2x-⅕ + 3y-2/4=2
{
3x+⅕ - 3y+2/4=0

1. Wyliczamy x z 1 równania
2x-⅕ + 3y-2/4=2
2x-0,2+3(x+7/10)-0,5=2
2x-0,2+3x+21/30-0,5=2
2x+3x = 2+0,2-0,7+0,5
5x=2 | :5
x = 0,4

2. Do 2 równania podstawiamy x
3x+⅕ - 3y+2/4=0
3*0,4+0,2 -3y + 0,5 = 0
1,2+0,2+0,5=3y
1,9=3y |:3
y = 0,6(3)

Mam nadzieje że dobrze.
1 5 1